Pharmacophore Mapping An Approach For Designing Cyclin Dependent Kinase 2 Inhibitors For Cancer Treatment - ASHISH SETHI; SACHDEV YADAV (International Journal of Pharma and Bio Sciences, 2010)
CDKs are serine/threonine kinases that play pivotal roles in cell cycle progression. Their timely activation and deactivation drives the cell through different stages of the cell cycle. The regulation of CDK activity is achieved by their association with cyclins, specific CDK inhibitors, their state of phosphorylation and ubiquitin mediated degradation. Several CDKs and cyclins have been identified, though only CDKs 1, 2, 4 and 6 are known to intervene in the cell cycle machinery.Majority of inhibitors target the ATP pocket of CDK2 and are labeled ATP-competitive inhibitors. Few CDK2 inhibitors have entered clinical trials and are displaying encouraging results.Virtual Screening (VS) is the computational analogue of biological screening. The main objective of VS is to help medicinal chemist filter out in actives from a library of compounds before going ahead for synthesis. An alternate approach to the above scheme involves extraction of common 3D features from a set of ligands, known as pharmacophore.